Exact traveling wave solutions of the Wu–Zhang system describing (1 + 1)-dimensional dispersive long wave - Kaplan, M.; Mayeli, P.; Hosseini, K. (Springer Science and Business Media LLC, 2017)
This paper examines the effectiveness of two newly developed algorithms called the exponential rational function and modified simple equation methods in exactly solving a well-known nonlinear system of partial differential equations. In this respect, the Wu–Zhang system which describes (1 + 1)-dimensional dispersive long wave is considered, and as an achievement, a series of exact traveling wave solutions for the aforementioned system are formally extracted.
Keywords: 13. Climate action